RESEARCH ON MEASUREMENT TECHNOLOGY OF CAPTO SHANK’S KEY DIMENSIONS USED IN HIGH SPEED MACHINING - ZHANG Jin; WANG ShuLin; SHI XiangYun; ZHOU YiJun (Jixie qiangdu)
In order to accomplish accurate measurement for Capto shank’s key dimensions, based on analyzing Standard ISO detailedly measurement parameters were determined and measurement system for Capto shank was designed. Positioning scheme was decided according to the idea about restraining the degrees of freedom in space, axial positioning was achieved by shank’s own weight, radial positioning was achieved by the rational configuration of three supporting nails, and circumferential positioning was achieved by controlling ring gauge’s cavity dimension strictly. Measurement for Capto shank with equal precision was done by using the developed measurement system, measurement results accorded with the accuracy requirement stipulated by ISO. Research shows that positioning method of the measurement system is feasible and can meet the demand of measurement for Capto shank’s key dimensions.